Health workers’ perception of digital technology use to improve mental health services - Olubunmi Y. Fashoto; Maureen N. Sibiya; Olanrewaju Oladimeji (Journal of Public Health in Africa, 2025)
Background: Integrating digital technologies into mental healthcare offers a transformative shift in the provision of online-based mental health services to Nigerians. This is crucial for Nigeria in order to minimise and curb the developing health emergency because of COVID-19.